Language inclusion and neo-colonialism: The impacts of ethnolinguistic admission criteria at South African universities - Dhlamini, Mbali Sunrise; Kaschula, Russell H (Critical Studies in Teaching and Learning, 2025)
Languages in South Africa have always been employed as stimuli to negotiate boundaries of unity and segregation among South Africans. Likewise, universities established before, during, and post-apartheid times were instituted either as key instruments to contrive separation among South Africans or as symbols to mend the segregation walls. This article set out to examine language distribution at South African universities, the language admission criteria and their impacts in promoting language inclusion and social cohesion in Departments of African Languages in the post-apartheid era. IsiNguni language modules were used to contextualise the study. A qualitative research approach was employed to carry out the research, using the interview schedule as an instrument to collect data. The Ethnolinguistic Vitality Theory was used to underpin the study. The findings revealed that African languages were predominantly distributed based on their official status in the South African provinces, while Afrikaans and particularly English were promoted across the country. The grade 12 certificate was the common criterion that was employed to admit or reject potential students’ applications to Departments of African Languages based on the home languages studied in grade 12. To some extent, the distribution of South African languages and the language admission approach to Departments of African languages were found to maintain the dominance of certain languages and ethnolinguistic segregation in the country. The article advocates for the promotion of African languages at a national rather than provincial level in order to uproot the ethnolinguistic traces of the apartheid government at South African universities.